Intersecting War, Education and Politics: Chinese Higher Education Policy during the Anti-Japanese War, 1931–1945 (KEMANUSIAAN The Asian Journal of Humanities, 2025)
During the Nanjing nationalist government period, the Ministry of Education established a developmental theme of “rectification” for higher education. Within this framework, each successive minister of education influenced the direction of higher education through their unique educational philosophies and policy approaches. From the onset of the Mukden Incident (1931) to the end of the Anti-Japanese War, three Ministers of Education—Zhu Jiahua, Wang Shijie and Chen Lifu—held notably long and stable terms. Their tenures and the implementation of their educational ideologies reflect not only the political manoeuvring within the upper echelons of the Kuomintang (KMT) but also the ongoing contest with the Chinese Communist Party (CCP). As Chiang Kai-shek’s position as “supreme leader” solidified, his control over educational administration evolved from limited influence to full authority. With the intensifying national crisis and the KMT government’s tightened control over education, liberalism in higher education entered a period of “dormancy”. The complex interplay between war, education and politics thus shaped the underlying factors driving shifts in higher education policies during this era.